Factors of Stress among Undergraduate Students during Movement Control Order - Suziana Hanini Sulaiman; Suhana Mohamed Lip; Shazarina Zdainal Abidin; Norshilawani Shahidan; Natasha Ariffin; Mohamad Fuad Haji Ishak; Sapie Sabilan (International Islamic Schools Alliance, 2021)
The implementation of Movement Control Order (MCO) to curb the spread of Covid-19 has various effects on the community, regardless of the field they are involved in. Enforcement order to stay at home has resulted to the closure and restriction of all types of operations including the education sector. Due to the implementation of MCO, the teaching and learning activities that used to be conducted face-to-face have been completely replaced by online learning. This situation eventually has given some stressful impact and has caused difficulties to students of higher learning institutions to continue their studies virtually. Various factors have been found as stressors among undergraduate students. It is hoped that this study would help to find effective ways to reduce stress among undergraduate students.